The Right of Self-Determination: Its Emergence, Development, and Controversy - Manan, Munafrizal (Mahkamah Konstitusi Republik Indonesia, 2015)
This paper discusses the right of self-determinationfrom international law and international human rights law perspective. It traces the emergence and development of self-determination from political principle to human right. It also explores the controversy of the right of self-determination. There have been different and even contradictory interpretations of the right of self-determination. Besides, there is no consensus on the mechanism to apply the right of self-determination. Both international law and international human rights law are vague about this.